Illocutionary Acts and Contextual Utterances in the Movie Raya and the Last Dragon - Ayu Ratri; Barli Bram (Pioneer: Journal of Language and Literature, 2022)
Understanding illocutionary acts in English can be challenging for EFL students. To understand illocutionary acts, EFL students can see how native speakers express utterances in their speech and understand the context that constructs the basis for using the illocutionary act. This study explored the types and contexts of utterances in the movie Raya and the Last Dragon. Data, consisting of 31 utterances, were collected from the movie transcript and analyzed using content analysis to classify illocutionary act types and contextual utterances. Results showed the movie characters usall five illocutionary acts, and the most dominant illocutionary act was the assertive type, which occurred 13 times. The context underlined the characters expressing illocutionary acts was the place, the interlocutor, the purpose of the conversation, the use of words, and the tone. This film type of verbal communication without text was direct speech or dialogue. This study offers relevant knowledge and benefits to EFL learners and teachers in the learning-teaching processes, such as creating familiarity with complex meanings in English to avoid misinterpretation, developing their consciousness of English utterances, and growing their capability to execute the speech act flawlessly.